1994
DOI: 10.3109/00016489409126050
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Fast Component of Vestibular Nystagmus During Childhood and Young Adulthood

Abstract: Primary nystagmus was evoked by constant angular acceleration at near-threshold levels (0.2, 0.4, and 0.6 degree/s2) in 34 normal human subjects (25 children aged 2-11 years and 9 young adults aged 17-21 years). Acceleration was carried out in complete darkness, and with subjects' eyes open. Analysis of response latencies showed that all subjects responded to acceleration magnitude as low as 0.2 degrees/s2. A decrease in response latency was associated with an increase in acceleration magnitude, and there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The numeric values of VVOR and VOR gain obtained in our study of 147 healthy children are used as normative data for children between 6 and 12 years old. With regard to our VVOR and VOR results, they are in accordance with the previous literature [Fuster et al, 1994;Sakaguchi et al, 1997;Bucci et al, 2004]. Following Sakaguchi et al [1997], VVOR gain does not depend on age, whereas VOR gain decreases with age.…”
Section: Sensory Organization Testssupporting
confidence: 82%
See 1 more Smart Citation
“…The numeric values of VVOR and VOR gain obtained in our study of 147 healthy children are used as normative data for children between 6 and 12 years old. With regard to our VVOR and VOR results, they are in accordance with the previous literature [Fuster et al, 1994;Sakaguchi et al, 1997;Bucci et al, 2004]. Following Sakaguchi et al [1997], VVOR gain does not depend on age, whereas VOR gain decreases with age.…”
Section: Sensory Organization Testssupporting
confidence: 82%
“…Other authors [Fuster et al, 1994;Sakaguchi et al, 1997;Zhang et al, 2007] have demonstrated a maturation of VOR with age.…”
mentioning
confidence: 99%